Different brain networks underlying intelligence in autism spectrum disorders. Issue 8 (17th April 2018) - Pua, Emmanuel Peng Kiat; Malpas, Charles B.; Bowden, Stephen C.; Seal, Marc L.
Abstract: There has been sustained clinical and cognitive neuroscience research interest in how network correlates of brain‐behavior relationships might be altered in Autism Spectrum Disorders (ASD) and other neurodevelopmental disorders. As previous work has mostly focused on adults, the nature of whole‐brain connectivity networks underlying intelligence in pediatric cohorts with abnormal neurodevelopment requires further investigation. We used network‐based statistics (NBS) to examine the association between resting‐state functional Magnetic Resonance Imaging (fMRI) connectivity and fluid intelligence ability in male children ( n = 50) with Autism Spectrum Disorders (ASD; M = 10.45, SD = 1.58 years and in controls ( M  = 10.38, SD = 0.96 years) matched on fluid intelligence performance, age and sex. Repeat analyses were performed in independent sites for validation and replication. Despite being equivalent on fluid intelligence ability to strictly matched neurotypical controls, boys with ASD displayed a subnetwork of significantly increased associations between functional connectivity and fluid intelligence. Between‐group differences remained significant at higher edge thresholding, and results were validated in independent‐site replication analyses in an equivalent age and sex‐matched cohort with ASD. Regions consistently implicated in atypical connectivity correlates of fluid intelligence in ASD were the angular gyrus, posterior middle temporal gyrus, occipital and temporo‐occipital regions. Development of fluid intelligence neural correlates in young ASD males is aberrant, with an increased strength in intrinsic connectivity association during childhood. Alterations in whole‐brain network correlates of fluid intelligence in ASD may be a compensatory mechanism that allows equal task performance to neurotypical peers.